The Effect of Powder Form and Sample Weight on the Acceptability of Yellow Melinjo (Gnetum gnemon L.) Peel Tea - Sulistiyani, Ade; Sartika, Rakhmi Setyani (Journal of Health and Nutrition Research, 2024)
Tea is one of the nutritious drinks that are popular with the Indonesian people. Recently, researchers have developed various new types of tea beyond the traditional tea plant (Camelia sinensis). One potential ingredient for tea development is melinjo peel, particularly the yellow melinjo peel, due to its strong antioxidant activity and superior α-glucosidase inhibitory activity. This study aims to investigate the influence of the powder form and sample weight on the acceptability of yellow melinjo (Gnetum gnemon L.) peel tea. The research employed an experimental method with a factorial completely randomized design (CRD) involving two factors. The first factor was the powder form of the tea (fine, semi-fine, and coarse), and the second factor was the sample weight (2.5 grams, 3 grams, and 5 grams). A hedonic test was conducted to assess the acceptability of yellow melinjo peel tea, involving 40 semi-trained panelists using a scale from 1 to 7 (strongly dislike to very much like). Data were analized using IBM SPSS 25.0 Statistics for Windows, with Kruskal-Wallis and Mann-Whitney tests at a significance level of P < 0.05. The results showed that both the powder form and sample weight of yellow melinjo peel tea significantly affected (P<0.05) taste, aroma, clarity, intensity, astringency, flavor, and overall acceptability, but did not significantly affect (P > 0.05) color and taste intensity. The most preferred formulation by panelists was yellow melinjo peel tea with a sample weight of 2.5 grams and a fine powder form, with an average score of 4.23 (like slightly).